2022
DOI: 10.3389/fcvm.2022.897771
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Hypertensive Disorders in Pregnancy and the Risk of Developing Chronic Hypertension

Abstract: ObjectiveThis meta-analysis comprehensively evaluated the association between hypertensive disorders in pregnancy (HDP) and the risk of developing chronic hypertension and the associations between specific types of HDP, including preeclampsia (PE) and gestational hypertension (GH), and the risk of developing chronic hypertension.DesignSystematic review and meta-analysis.Data SourcesThe PubMed, Embase and Cochrane Library databases were searched from inception to August 20, 2021.MethodsDepending on heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Furthermore, hypertensive disorders of pregnancy and gestational diabetes are established risk factors for future risk of corresponding chronic health conditions 22 49 50. The results of this study showed a strong association in the fully adjusted model (online supplemental table S4; HDP with hypertension, aHR 5.05, 95%CI 3.16 to 8.07; GDM with T2DM, aHR 18.80, 95%CI 12.05 to 29.35).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, hypertensive disorders of pregnancy and gestational diabetes are established risk factors for future risk of corresponding chronic health conditions 22 49 50. The results of this study showed a strong association in the fully adjusted model (online supplemental table S4; HDP with hypertension, aHR 5.05, 95%CI 3.16 to 8.07; GDM with T2DM, aHR 18.80, 95%CI 12.05 to 29.35).…”
Section: Discussionmentioning
confidence: 59%
“…These were GDM and hypertensive disorders of pregnancy (including chronic hypertension, gestational hypertension, preeclampsia, eclampsia and HELLP syndrome). Additional file 1 : Table S8 [ 14 17 , 112 117 ] includes the definitions of the exposures and the extent of other confounders adjusted for in the reviews included. The number of women included in the systematic reviews ranged between 1,332,373 and 3,095,457 for studies relating to postpartum T2DM while for hypertension it was between 8041 and 2,711,443 (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… Hypertensive disorders of pregnancy (gestational hypertension and preeclampsia, not chronic hypertension.) Women with prior normotensive pregnancies, preeclampsia without severe features, or late-onset preeclampsia (developed after 34 completed weeks of gestation) depending on individual included studies Women with history of pregnancy (215,528) Hypertension Cohort (37) Newcastle–Ottawa Scale Thailand Science Research and Innovation (TSRI) Research Career Development Grant and Prince of Songka University High Xu 2022 [ 112 ] Brazil, Britain, China, France, Japan, Jordan, The Netherlands, Pakistan, Spain, Sweden, USA To comprehensively evaluate the association between hypertensive disorders in pregnancy and the risk of developing chronic hypertension. Hypertensive disorders of pregnancy or with the specific types of gestational hypertension and preeclampsia Women without hypertensive disorders of pregnancy or specific types of preeclampsia and gestational hypertension Women with history of pregnancy (hypertensive disorders of pregnancy as exposure = 228,317, preeclampsia as exposure = 341,060, gestational hypertension as exposure = 933) Hypertension Hypertensive disorders of pregnancy Cohort (5) Case–control (5) Cross-sectional (1) Gestational hypertension; cohort (1) Case–control (2) Preeclampsia; cohort (10) Case–control (3) Newcastle–Ottawa Scale National Natural Science Foundation of China High Vounzoulaki 2020 [ 114 ] Australia, Canada, Finland, France, Hungary, India, Iran, Israel, Italy, Korea, Pakistan, Spain, Sri Lanka, Sweden, UK, USA To estimate and compare progression rates to type 2 diabetes mellitus (T2DM) in women with gestational diabetes mellitus (GDM) and healthy controls Gestational diabetes mellitus Women with normoglycemic pregnancy Women with history of pregnancy (1,332,373) T2DM Cohort (20) Newcastle–Ottawa Scale National Institute for Health Research High Zhao 2021 [ 115 ] Australia, Canada, Denmark, Finland, Netherlands, Norway, Sweden, Taiwan, UK, USA To quant...…”
Section: Resultsmentioning
confidence: 99%
“…Researchers are gradually focusing on patients with hypertension but not enough to diagnose PE while studying the eld of PE management; for example, hypertension in pregnancy has a higher risk of developing chronic hypertension in the postpartum period relative to PE [44] . While studying PE, FGR as a complication of PE has often received attention during PE management [45] .…”
Section: Discussionmentioning
confidence: 99%